2018
DOI: 10.18502/kls.v4i1.1360
|View full text |Cite
|
Sign up to set email alerts
|

Toddlers’ Eating Behavior in Slum Urban and Semi Urban Communities: Study in Kampung Melayu and Bantul, Indonesia

Abstract: Toddlers’ eating behavior is influenced by many factors. This study aimed to determine food consumption behavior of toddlers in the urban slum (Kampung Melayu) and semi urban slum (Bantul). The study used the Rapid Assessment Procedure qualitative approach. The informants were mothers or toddler sitters, health workers, and local community leaders. The results showed that in slum urban areas, there was a tendency for parents to give children options to decide for themselves how much and what foods they wanted.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A recent survey among mothers of young children in Bandung City, Indonesia, found that mothers who fed their young child a GUM reported that perceived growth and health benefits were important factors for their decision to feed this product (Helen Keller International, 2021), and a qualitative study noted that caregivers of Indonesian young children reported GUMs to be vital to the health of their child (Martha, Amelia, & Myranti, 2017). Although GUM products are often fortified with micronutrients commonly deficient in young child diets in low-income countries like Indonesia (Fahmida et al, 2014), the overall nutrient profile of the products cannot be considered appropriate for young children, particularly when considering the growing concerns of childhood obesity in these same contexts (National Population and Family Planning Board et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…A recent survey among mothers of young children in Bandung City, Indonesia, found that mothers who fed their young child a GUM reported that perceived growth and health benefits were important factors for their decision to feed this product (Helen Keller International, 2021), and a qualitative study noted that caregivers of Indonesian young children reported GUMs to be vital to the health of their child (Martha, Amelia, & Myranti, 2017). Although GUM products are often fortified with micronutrients commonly deficient in young child diets in low-income countries like Indonesia (Fahmida et al, 2014), the overall nutrient profile of the products cannot be considered appropriate for young children, particularly when considering the growing concerns of childhood obesity in these same contexts (National Population and Family Planning Board et al, 2018).…”
Section: Discussionmentioning
confidence: 99%